Análisis y evaluación del modelo de emprendimiento del Bar Universidad Politécnica Salesiana Campus Sur, Sede Quito periodo 2010 - 2013 - Álvarez Duque, Juan Pablo (2014)
The bar at the Salesian University, South Campus in 2010 presented a process of deterioration both in service and the quality and variety of products expendían here. What motivated the development of the "Re-alignment and Re-structuring of the bar of the Salesian Polytechnic University, South Campus" project developed by students of the institution of the School of Engineering in Management and Leadership